Prospective study on Maresin-1 and cytokine levels in medication-naïve adolescents with first-episode major depressive disorder - Qiu, Tian; Li, Xiao; Chen, Wanjun; He, Jinglan; Shi, Lei; Zhou, Chenxi; Zheng, Anhai; Lei, Zhongli; Tang, Chenglu; Yu, Qingchan; Du, Lian; Guo, Jiamei (Frontiers in Psychiatry, 2023)
Background: Inflammation and immune activation may play a role in the pathological mechanism of Major Depressive Disorder (MDD). Evidence from cross-sectional and longitudinal studies of adolescents and adults has shown that MDD is associated with increased plasma pro-inflammatory cytokines (e.g., IL-1β, IL-6). It has been reported that Specialized Pro-resolving Mediators (SPMs) mediate inflammation resolution, and Maresin-1 can activate the process of inflammation and promote inflammation resolution by promoting macrophage phagocytosis. However, no clinical studies have been conducted to evaluate the relationship between the levels of Maresin-1 and cytokine and the severity of MDD symptomatology in adolescents. Methods: 40 untreated adolescent patients with primary and moderate to severe MDD and 30 healthy participants as the healthy control (HC) group) aged between 13 and 18 years old were enrolled. They received clinical and Hamilton Depression Rating Scale (HDRS-17) evaluation and then, blood samples were collected. Patients in the MDD group were re-evaluated for HDRS-17, and blood samples were taken after a six to eight-week fluoxetine treatment. Results: The adolescent patients with MDD had lower serum levels of Maresin-1 and higher serum levels of interleukin 6 (IL-6) compared with the HC group. Fluoxetine treatment alleviated depressive symptoms in MDD adolescent patients, which was reflected by higher serum levels of Maresin-1 and IL-4 and lower HDRS-17 scores, serum levels of IL-6, and IL-1β. Moreover, the serum level of Maresin-1 was negatively correlated with the depression severity scores on the HDRS-17. Conclusions: Adolescent patients with primary MDD had lower levels of Maresin-1 and higher levels of IL-6 compared with the HC group, implying that the peripheral level of pro-inflammatory cytokines may be elevated in MDD, resulting in the insufficiency of inflammation resolution. The Maresin-1 levels increased after anti-depressant treatment, whereas IL-6, IL-1β, and IL-4 levels decreased significantly. Moreover, Maresin-1 level negatively correlated with depression severity, suggesting that reduced levels of Maresin-1 promoted the progression of MDD.